A hybrid clock group communication protocol. (1st January 2014) - Duolikun, Dilawaer; Aikebaier, Ailixier; Takizawa, Makoto
In distributed systems, a group of multiple processes are required to cooperate with each other. Here, each process is peer and directly exchanges messages with other processes without centralised coordination. Each process has to causally deliver messages in a scalable group. Messages can be causally delivered to every process in linear clock (LC) and vector (VC) protocols. Here, some pair of messages ordered in the LC protocol may not be causally related, i.e., unnecessarily ordered. In this paper, we discuss a hybrid clock (HC) protocol to causally deliver messages in a scalable group in order to reduce the number of unnecessarily ordered messages. The HC protocol takes advantage of the LC and physical clock (PC) protocols. We show unnecessarily ordered messages can be reduced in the HC protocol compared with the LC protocol through experimentation.